2013
DOI: 10.12942/lrsp-2013-5
|View full text |Cite
|
Sign up to set email alerts
|

The Heliospheric Magnetic Field

Abstract: The heliospheric magnetic field (HMF) is the extension of the coronal magnetic field carried out into the solar system by the solar wind. It is the means by which the Sun interacts with planetary magnetospheres and channels charged particles propagating through the heliosphere. As the HMF remains rooted at the solar photosphere as the Sun rotates, the large-scale HMF traces out an Archimedean spiral. This pattern is distorted by the interaction of fast and slow solar wind streams, as well as the interplanetary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
199
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 222 publications
(210 citation statements)
references
References 264 publications
(268 reference statements)
9
199
0
2
Order By: Relevance
“…This paper highlights some key results obtained on the variable phenomena in the Sun-Earth system during the CAWSES-II time frame. Detailed treatment of topics relevant to CAWSES-II can be found in the Living Reviews in Solar Physics: Hathaway (2010), Charbonneau (2010), Petrovay (2010), Chen (2011), Shibata and Magara (2011), Aschwanden (2011), Webb and Howard (2012), Usoskin (2013), Potgieter (2013), Lockwood (2013), Owens and Forsyth (2013).…”
Section: Methodsmentioning
confidence: 99%
“…This paper highlights some key results obtained on the variable phenomena in the Sun-Earth system during the CAWSES-II time frame. Detailed treatment of topics relevant to CAWSES-II can be found in the Living Reviews in Solar Physics: Hathaway (2010), Charbonneau (2010), Petrovay (2010), Chen (2011), Shibata and Magara (2011), Aschwanden (2011), Webb and Howard (2012), Usoskin (2013), Potgieter (2013), Lockwood (2013), Owens and Forsyth (2013).…”
Section: Methodsmentioning
confidence: 99%
“…At present, the dynamics occurring in the deeper interior are probed only by helioseismology, allowing in principle the inference of links between deep-seated phenomena and surface ones (see Living Review by Gizon and Birch 2005). Such intense magnetism, and its associated complex and time varying geometry, lead to a complex coronal structure, many eruptive events (flares, coronal mass ejection [CMEs]), and shapes the solar wind and the heliosphere (see Living Reviews by Cranmer 2009;Owens and Forsyth 2013). Over an 11-year cycle various measures with satellites like Ulysses, IBEX, Voyager I & II or ground based radio observations have demonstrated that the space environment surrounding the Sun drastically changes.…”
Section: The Sun: Dynamics and Magnetism Over Timementioning
confidence: 99%
“…The one free Lockwood et al (2014a). This approach has shown to be successful in reconstructing the observed near-Earth heliospheric magnetic field intensity, B, over both the space age and the extended geomagnetic reconstruction period (Owens & Forsyth 2013;Lockwood & Owens 2014;Usoskin et al 2015). Panel (a) of Figure 4 shows the R G *, the corrected group sunspot number (Lockwood et al 2014b).…”
Section: Reconstructing the Heliospheric Magnetic Fieldmentioning
confidence: 99%